An Investigation of Rainfall-Induced Landslides From the Pre-Failure Stage to the Post-Failure Stage Using the Material Point Method - Lee, Wei-Lin; Martinelli, Mario; Shieh, Chjeng-Lun (Frontiers in Earth Science, 2021)
The kinematic behavior of rainfall-induced landslides from the pre-failure stage to post-failure stage contains important information for risk assessment and management. Because a complex relationship exists between rainfall conditions, pore water pressure, soil strength, and movement rates, a numerical model is the most efficient way to investigate the behavior of rainfall-induced landslides. In this study, the material point method (MPM) is used to investigate the dynamic behavior of landslides. First, the rainfall boundary conditions are extensively verified by comparing 1-D consolidation tests against other numerical solutions. Then, a numerical model is used to simulate a lab-scale rainfall-induced slope failure. A parametric study shows the influence of rainfall intensity on pore water pressure development, failure triggering time, surface displacement, and velocity. The use of the MPM provides a clear understanding in the failure mechanism and post-failure behavior of a rainfall-induced landslide.